Efektivitas Penggunaan Media Pembelajaran Interaktif untuk Pembelajaran Pendidikan Pancasila di SD - Ngurah Ardiawan, I Ketut; Lesmana Putra, Kadek Joni; Rian Indrawan, Putu; Darma Yoga, Gede (IJPSE Indonesian Journal of Primary Science Education, 2025)
This study examines the effectiveness of using interactive learning media in Pancasila education for fourth-grade students at SDN 1 Anturan Singaraja. The results of interviews and observations indicate that interactive media can enhance students' attention, engagement, and understanding compared to conventional methods. Visually and auditorily appealing animations help students connect theoretical concepts with everyday life, making learning more effective and enjoyable. However, challenges such as limited internet access and a lack of alignment between content and local culture hinder its optimal use. Therefore, recommended solutions include improving school network facilities, developing more contextually relevant learning media, and providing teacher training in creating interactive media. Additionally, university students as future educators are expected to master digital technology to create innovative teaching methods. Thus, the use of interactive learning media is expected to comprehensively improve the quality of Pancasila education in elementary schools.